Reading Workshop-Based Interactive Materials for Enhancing Reading Comprehension in Indonesian Language Learning - Ambarwati, Aniza; Wati, Unik Ambar (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2025)
The reading ability of elementary school students in Indonesia is low. Ineffectiveness in reading learning is one of the causes of the low reading comprehension ability of fifth-grade elementary school students. Therefore, interactive teaching materials are needed that guide students to improve their reading comprehension skills. This study aims to develop interactive teaching materials based on reading workshops that are suitable for use in learning, to determine the practicality and effectiveness of interactive teaching materials based on reading workshops, and to test the effectiveness of interactive teaching materials based on reading workshops in Indonesian language learning elements of reading on the reading comprehension ability of grade V elementary school students. The type of research used was Research and Development (R&D), which adapted the Borg & Gall development model. The study subjects were 39 grade V elementary school students in Karanganyar, Kebumen, Central Java. The data collection technique in this study used tests, interviews, observations, and scales (questionnaires). The analysis techniques used were descriptive analysis, t-test with independent sample t-test, paired sample t-test, and N-gain score. The results of the study show that: 1) the products of research and development in the form of interactive teaching materials based on reading workshops are feasible and practical for use in Grade V Indonesian language learning; 2) the product has proven to be effective in improving the reading comprehension skills of fifth-grade elementary school students; and 3) there is a significant effect on reading comprehension ability, as indicated by a significance value of 0.000 < 0.05, demonstrating that reading workshop-based teaching materials effectively enhance students’ reading comprehension skills. This study contributes to the field of language education by providing empirical evidence that integrates the reading workshop approach with interactive teaching materials as an effective instructional model for improving elementary students’ reading comprehension.